2020
DOI: 10.1002/adfm.202002281
|View full text |Cite
|
Sign up to set email alerts
|

PtCo@NCs with Short Heteroatom Active Site Distance for Enhanced Catalytic Properties

Abstract: The crucial issue for fuel cells is to improve the activity and durability of Pt-based catalysts. Herein, based on the short distance enhancement effects, a novel PtCo@NC catalyst with remarkably enhanced electrocatalytic properties for methanol oxidation reaction (MOR) in acidic electrolytes is developed by shortening the Pt-Co active site distance. In brief, a series of PtCo@NC catalysts with different Pt-Co biatomic arrangement are precisely synthesized by an in situ reduction-fusion method, achieving Pt-Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 47 publications
4
55
0
Order By: Relevance
“…[40] Besides,l ittle oxides and hydroxides of Co (that is,C oO, Co 3 O 4 ,orCo(OH) 2 )isdetected on the surface of the catalysts, may resulting from cyanuric acid chelated on surface.X PS investigation of the Pt 4f spectrum (Figure 4h)r evealed the presence of metallic Pt, whereby two intense peaks were located at 71.8 and 75.2 eV,c orresponding to Pt 0 4f 7/2 and Pt 0 4f 5/2 ,respectively. [36,41] In the case of RuCo/C (Supporting Information, Figure S24), similar results were obtained to those for PtCo/C,a nd ruthenium existed mainly in the metallic Ru form. [34,42] These results again indicated that the etching processes of H 2 PtCl 6 and RuCl 3 were similar.…”
Section: Angewandte Chemiesupporting
confidence: 79%
See 3 more Smart Citations
“…[40] Besides,l ittle oxides and hydroxides of Co (that is,C oO, Co 3 O 4 ,orCo(OH) 2 )isdetected on the surface of the catalysts, may resulting from cyanuric acid chelated on surface.X PS investigation of the Pt 4f spectrum (Figure 4h)r evealed the presence of metallic Pt, whereby two intense peaks were located at 71.8 and 75.2 eV,c orresponding to Pt 0 4f 7/2 and Pt 0 4f 5/2 ,respectively. [36,41] In the case of RuCo/C (Supporting Information, Figure S24), similar results were obtained to those for PtCo/C,a nd ruthenium existed mainly in the metallic Ru form. [34,42] These results again indicated that the etching processes of H 2 PtCl 6 and RuCl 3 were similar.…”
Section: Angewandte Chemiesupporting
confidence: 79%
“…01‐1278). This phase transition of Co may originate from alloying with Pt and Ru, which again indicates that the introduced Pt and Ru were dissolved in the metallic Co to form alloys [36, 37] . Furthermore, the XRD results (Supporting Information, Figure S22c) of PdCo/C indicate the presence of Co 3 O 4 (JCPDS No.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Clearly, different metals may serve different roles and work in a synergetic way to bring excellent NRR performance. Moreover, HEA can shorten the distance between active sites [ 51 ] and provide a huge space for component optimization, advanced knowledge for such a synergetic role between metals can greatly help the rational design of catalysts.…”
Section: Resultsmentioning
confidence: 99%